Knowledge and attitude regarding needle stick injury among pediatric nurses at Hospital Universiti Sains Malaysia - Ghani, Nurul Afarah (Universiti Sains Malaysia, 2015)
Needle stick injury is a challenging issue among health care workers especially the nurses. Nurses' knowledge and attitude regarding NSI seem affect them to get injury. A cross sectional study, descriptive study was carried out to assess the knowledge and attitude of nurses regarding needle stick injury. Total of 73 nurses in pediatric units completed the questionnaires by purposive selection technique that fits the inclusion criteria. Data was statically analyzed using the software package SPSS version 20.0. Statistical significance was considered at p value < 0.05. Among 73 participants, 72 (98.6%) participants had high knowledge, while the remaining 1 (1.4%) participant had moderate knowledge. There were 71 (97.3%) of participants had good attitude, whereas 2 (2.7%) participants had moderate attitude. Fisher's Exact Test showed no significant association between level of education and knowledge level (p>0.05). and attitude level (p>0.05). Besides, Fisher's Exact Test also showed no significant association between work experience and knowledge level (p>0.05) and attitude level (p>0.05). In conclusion, this research finding indicated there was no association between level of education with knowledge and attitude among nurses in pediatric units. Moreover, no association found in this research between work experience with knowledge and attitude among pediatric nurses in Hospital USM. Hence, further research is required to confirm findings and improve the knowledge and attitude among nurses regarding needle stick injury.